Aqueous zinc-manganese battery electrolyte and preparation and application thereof
Through the combined treatment of sulfuric acid modified diatomaceous earth with zinc salt and manganese salt, the corrosion and dissolution problems caused by water activity in water-based zinc-manganese batteries are solved, significantly improving the battery capacity and cycle stability and extending the battery life.
Patent Information
- Application Number
- CN202411290522.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
AI Technical Summary
The high water activity of aqueous zinc-manganese batteries leads to corrosion of zinc negative electrodes, side reactions and positive electrode dissolution, resulting in rapid capacity decay and short cycle life.
Sulfuric acid modified diatomaceous earth is combined with zinc salt and manganese salt to regulate chemical composition and microstructure, destroy the hydrogen bond network of water, inhibit the activity of water, reduce hydrogen evolution and side reactions, promote the deposition of zinc ions, and limit the domain to bind zinc Ions change the electric field around the electrode to prevent the formation of zinc dendrites.
It significantly improves the capacity, cycle stability and batch quality stability of the battery, extends the service life of zinc-manganese batteries, reduces the occurrence of side reactions, and improves the circulation performance of the battery.
Smart Images

Figure CN119170896A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery materials, and in particular to the field of battery liquid electrolytes. Background Art
[0002] Energy is considered to be one of the three pillars of human social development, so energy storage technology is particularly important. Lithium-ion batteries, as the mainstream electrochemical energy storage device on the market, are widely used in electric vehicles and energy storage power systems such as hydropower, thermal power, wind power and solar power stations. Currently, many problems limit the prospects of lithium-ion batteries. First, lithium resources severely limit their large-scale energy storage applications. Second, the energy density of lithium-ion batteries is close to the theoretical limit. Third, the flammability of commercial organic electrolytes poses a major challenge to their safety. Zinc-ion batteries have a high theoretical capacity (820mAh g -1 ), low cost, large reserves, safety, low toxicity, etc. Therefore, zinc-ion batteries have great development prospects in the field of large-scale energy storage.
[0003] There are three general types of electrolytes: solid electrolytes, quasi-solid electrolytes, and liquid electrolytes (also known as electrolytes). Compared with solid electrolytes, liquid electrolytes and quasi-solid electrolytes (such as gel electrolytes) have very excellent ionic conductivity, making Zn 2+ The migration rate is fast, the rate performance is good, the battery polarization is small, and its preparation process is simple and the cost is low. However, for aqueous zinc-manganese batteries, the use of commonly used aqueous electrolytes such as ZnSO4 or Zn(CF3SO3)2, etc., due to their high content of active water, leads to greater corrosion to the zinc negative electrode, and often causes problems such as deformation of the zinc negative electrode, dendrites, and hydrogen evolution, which leads to rapid capacity decay and reduced cycle life of the zinc-manganese battery, causing it to fail quickly and cannot be used on a large scale. For positive electrode materials, the dissolution of manganese-based positive electrode materials leads to rapid decay of battery capacity, resulting in poor cycle performance and short battery life of aqueous zinc-manganese batteries. Summary of the invention
[0004] In view of the defects of the existing aqueous zinc-manganese battery in which the water activity in the aqueous electrolyte is high and it is easy to cause the negative electrode corrosion, side reactions, positive electrode dissolution and other characteristics resulting in insufficient capacity and cycle stability, the present invention provides an electrolyte for an aqueous zinc-manganese battery, aiming to provide an electrolyte that can improve the battery capacity, cycle stability and batch quality stability.
[0005] The second object of the present invention is to provide the preparation and application of the electrolyte of the aqueous zinc-manganese battery.
[0006] A third object of the present invention is to provide an aqueous zinc-manganese battery comprising the electrolyte.
[0007] Unlike solid and semi-solid electrolytes, the water in the electrolyte of aqueous zinc-manganese batteries is more active, which will increase the risk of zinc negative electrode corrosion and positive electrode material dissolution, thereby affecting the battery capacity and cycle stability. In response to this problem, the inventors previously tried to directly add diatomaceous earth to the electrolyte to prepare the electrolyte. However, early studies have shown that inappropriate diatomaceous earth addition is difficult to achieve the expected technical effect. The main reasons are: (a) The structural characteristics of diatomaceous earth are difficult to naturally adapt to the use requirements of aqueous electrolytes; (b) Diatomaceous earth has a complex composition, which contains components that are beneficial, unhelpful, and harmful to electrochemical performance. Inappropriate processing technology makes it difficult to selectively remove harmful components and retain the beneficial components as much as possible, making it difficult to exert its performance advantages. In response to the problems faced by diatomaceous earth in the process of adding diatomaceous earth to aqueous electrolytes, the present invention has developed the following improvement schemes after in-depth research:
[0008] An electrolyte for an aqueous zinc-manganese battery comprises sulfuric acid-modified diatomaceous earth, zinc salt, manganese salt and water, wherein the content of the sulfuric acid-modified diatomaceous earth is 5-25wt%.
[0009] The innovative research of the present invention shows that the diatomite is modified with sulfuric acid in advance, so that its chemical composition and microstructure can be effectively regulated, and then it is combined with zinc salt and manganese salt, and the content of the diatomite modified by sulfuric acid is further coordinated with the joint control, so that unexpected synergy can be achieved, the hydrogen bond network of water can be destroyed, the activity of water can be inhibited, the corrosion of the aqueous electrolyte to the pole piece can be reduced, and the occurrence of hydrogen evolution and side reactions in the solution can be significantly reduced, and the desolvation process of hydrated zinc ions can be accelerated, and the rapid deposition of zinc ions can be promoted, and the dissolution of the positive electrode material can be alleviated. In addition, the zinc ions can be confined and bound, the electric field around the electrode can be changed, and the "tip effect" can be suppressed to prevent the formation of zinc dendrites at the zinc negative electrode interface. Through the sulfuric acid-modified diatomite and its concentration described in the present invention and the combination of zinc salt and manganese salt, the capacity, cycle stability and process batch quality stability of the battery can be significantly improved in a coordinated manner.
[0010] In the present invention, the diatomaceous earth is preliminarily washed with water and then modified by soaking in sulfuric acid, followed by solid-liquid separation and water washing to obtain the sulfuric acid-modified diatomaceous earth.
[0011] The research of the present invention unexpectedly shows that the innovative use of sulfuric acid for modification treatment can unexpectedly further regulate the microstructure of diatomaceous earth, and is also beneficial to the highly selective hybridization modification of its beneficial components, compared with non-modification and similar hydrochloric acid modification treatments. The concentration of diatomaceous earth and the combination of zinc salts and manganese salts can further synergistically improve the capacity, cycle stability and batch quality stability of aqueous electrolytes.
[0012] In the present invention, the concentration of the solute in the sulfuric acid solution is 5 to 20 wt.%.
[0013] In the present invention, the soaking process is carried out under stirring;
[0014] Preferably, the soaking time is 6 to 24 hours; preferably 10 to 15 hours.
[0015] In the present invention, after soaking, solid-liquid separation (such as filtration or centrifugation) is performed to obtain a solid, which is then washed with water until the filtrate is neutral and then dried to obtain the acid-modified diatomaceous earth.
[0016] In the present invention, based on the unexpected adaptation innovation of the sulfuric acid-modified diatomaceous earth and the aqueous zinc-manganese battery, the content of the sulfuric acid-modified diatomaceous earth in the electrolyte is further controlled to be 18-22wt%, which can unexpectedly further achieve synergy and further improve the capacity, cycle stability and batch quality stability of the aqueous zinc-manganese electrolyte.
[0017] In the present invention, the zinc salt and manganese salt can be any water-soluble electrolyte containing zinc and manganese in the industry.
[0018] For example, in the present invention, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, zinc nitrate, and zinc perchlorate. The manganese salt is one or more of manganese sulfate and manganese chloride.
[0019] In the present invention, in the electrolyte, the concentration of the zinc salt is 1 mol / L to 3 mol / L, preferably 1.5 mol / L to 2.5 mol / L. The concentration of the manganese salt is 0.05 mol / L to 1 mol / L, more preferably 0.075 mol / L to 0.125 mol / L.
[0020] The present invention also provides a method for preparing the electrolyte, which is obtained by uniformly mixing diatomaceous earth, zinc salt, manganese salt and water. During the preparation process, the system mixing can be accelerated by existing methods, for example, the mixing process is carried out under stirring and / or ultrasound assistance.
[0021] The present invention also includes the application of the electrolyte, which is used as an electrolyte to prepare an aqueous zinc-manganese battery.
[0022] The present invention also provides an aqueous zinc-manganese battery, which comprises the electrolyte of the present invention.
[0023] The aqueous zinc-manganese battery of the present invention has conventional components, principles and operations except that the electrolyte of the present invention is added to the electrolyte.
[0024] The electrolyte of the present invention, based on the combination of the sulfuric acid-modified diatomaceous earth and its content, zinc salt and manganese salt, can achieve synergy, can reduce the activity of water in the aqueous electrolyte, reduce the occurrence of side reactions in the solution, inhibit the corrosion of the zinc negative electrode, and alleviate the dissolution of the positive electrode material, so that it can obtain more stable cycle performance and more cycles, and improve the service life of the aqueous zinc-manganese battery. The preparation method is simple, the cost is low, the raw materials are abundant, and it has broad industrial prospects.
[0025] In the present invention, in the aqueous zinc-manganese battery, the manganese element in the electrolyte is 0.9 to 2.5 times the weight of the manganese element in the positive electrode of the aqueous zinc-manganese battery; preferably 0.95 to 1.1 times.
[0026] The present invention also shows that the innovative use of sulfuric acid to modify diatomaceous earth and the control of the amount of diatomaceous earth introduced and the corresponding amount of electrolyte added to the battery can further synergistically improve the capacity, cycle stability and batch quality stability of the resulting aqueous zinc-manganese battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The long cycle performance diagram of the aqueous zinc-manganese battery assembled with the electrolyte of Example 1;
[0028] Figure 2 This is a long cycle performance diagram of the aqueous zinc-manganese battery assembled in Example 2 at 200 mA / g;
[0029] Figure 3 This is a long cycle performance diagram of the aqueous zinc-manganese battery assembled in Example 2 at 500 mA / g;
[0030] Figure 4 Long cycle performance diagram of aqueous zinc-manganese batteries at 200 mA / g for multiple batches of batteries assembled in Example 3;
[0031] Figure 5 The long cycle performance diagram of the aqueous zinc-manganese battery assembled with the electrolytes of Comparative Example 1 and Comparative Example 2;
[0032] Figure 6 is the SEM image of diatomite before and after modification in comparative example 3;
[0033] Figure 7 This is a long cycle performance diagram of the aqueous zinc-manganese battery assembled in Comparative Example 3;
[0034] Figure 8 This is the long cycle performance diagram of the aqueous zinc-manganese battery assembled in Comparative Example 4. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments further describe the content of the present invention in detail, and the protection scope of the claims of the present invention is not limited by the embodiments.
[0036] In the present invention, the performance test method of aqueous zinc-manganese battery is as follows: manganese dioxide active material, conductive agent Ketjen black, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1, and after sufficient grinding, N-methyl-2-pyrrolidone (NMP) is added to form a uniform black paste slurry, which is coated on a stainless steel mesh and dried for 12 hours as a positive electrode, wherein the loading of the active material is 0.8-1.0 mg cm -2 , zinc sheet was used as negative electrode, the prepared electrolyte was used as electrolyte, and the separator was assembled into a CR2016 button battery. The charge and discharge current density used to test the cycle performance was 200mA / g~500mA / g, and the test temperature was room temperature.
[0037] Example 1
[0038] Sulfuric acid modified diatomaceous earth:
[0039] First, untreated diatomaceous earth was dissolved in deionized water, stirred continuously for 3 hours under magnetic stirring conditions, washed with water, treated with 15% sulfuric acid for 3 hours, filtered, washed with water until the pH was neutral, and then the diatomaceous earth was placed at 80°C and vacuum dried for 12 hours to obtain sulfuric acid-modified diatomaceous earth.
[0040] Electrolyte: Sulfuric acid-modified diatomaceous earth, zinc sulfate and manganese sulfate are uniformly dispersed in water to obtain (the dispersion process is, for example, ultrasonically treating the solution for 10 minutes, stirring continuously for 12 hours under magnetic stirring conditions, and then ultrasonically treating the solution for 10 minutes.
[0041] In the electrolyte, the concentration of zinc sulfate is 2 mol / L, the concentration of manganese sulfate is 0.1 mol / L, and the sulfuric acid-modified diatomaceous earth accounts for 20% of the weight of the electrolyte.
[0042] During the injection phase of battery assembly, the battery was divided into the following four experimental groups according to the amount of electrolyte injected:
[0043] Group A: The amount of Mn element in the injected electrolyte is the same as the weight of Mn element in the positive electrode active material;
[0044] Group B: The amount of Mn element in the injected electrolyte is 1.5 times the weight of Mn element in the positive electrode active material;
[0045] Group C: The amount of Mn element in the injected electrolyte is twice the weight of Mn element in the positive electrode active material;
[0046] Group D: The amount of Mn element in the injected electrolyte is 2.5 times the weight of Mn element in the positive electrode active material;
[0047] The cycle performance data of batteries in groups A to D are shown in Figure 1 ;pass Figure 1 It can be seen that when the amount of manganese in the injected electrolyte is the same as that in the positive electrode, better electrochemical performance can be obtained.
[0048] Example 2
[0049] Compared with Example 1A, the only difference is that the content of sulfuric acid-modified diatomaceous earth in the electrolyte is adjusted. The experimental groups are:
[0050] Group A: 10% by weight of sulfuric acid-modified diatomaceous earth based on the electrolyte;
[0051] Group B: 15% by weight of sulfuric acid-modified diatomaceous earth based on the electrolyte;
[0052] Group C: 20% by weight of sulfuric acid-modified diatomaceous earth based on the electrolyte;
[0053] Group D: diatomaceous earth modified with sulfuric acid is 25% by weight of the electrolyte;
[0054] Test results see Figure 2 and Figure 3 .
[0055] Figure 2 It is a cycle performance diagram of a battery made of the electrolyte material of Example 1. At a current density of 200 mA / g, after 500 stable cycles, its capacity retention rate is still 86.2%, and its coulombic efficiency is also relatively stable. Figure 3 When the current density is increased to 500 mA / g, after 500 stable cycles, the discharge capacity is still 177.5 mAh / g, indicating that when the amount of diatomaceous earth introduced accounts for 20% of the mass of the electrolyte, it has better cycle performance.
[0056] Example 3
[0057] Compared with Example 1A, the process of Example 1A was repeated to prepare and assemble three batches of batteries, and the conditions of each batch were the same as those of Example 1A. Tests were carried out according to the above scheme to evaluate the quality stability of the technical scheme.
[0058] Test results see Figure 4 ,pass Figure 4 It can be seen that the process of the present invention has excellent batch quality stability.
[0059] Example 4
[0060] Compared with Example 1A, the only difference is that the concentration of zinc sulfate in the electrolyte is adjusted to 2.5 M, and the concentration of manganese sulfate is adjusted to 0.12 M, and the other operations and parameters are the same as those in Example 1. It can obtain similar results to those in Example 1A.
[0061] Comparative Example 1
[0062] Compared with Example 1A, the only difference is that the electrolyte is replaced with a 2 mol / L zinc sulfate aqueous solution. The injection amount of the electrolyte and other conditions are the same as in Example 1.
[0063] Comparative Example 2
[0064] Compared with Example 1A, the only difference is that the electrolyte is replaced with a mixed water of 2 mol / L zinc sulfate and 0.1 mol / L manganese sulfate. The injection amount of the electrolyte (the injection amount of Mn) and other conditions are the same as those in Example 1.
[0065] The battery was tested for cycle performance in the LAND electrochemical test system. The battery charge and discharge range was 0.8V to 1.8V, and the current density was 200mA / g for charge and discharge (the same below). Figure 5 shown.
[0066] It can be found that the introduction of manganese sulfate solution greatly improved the specific capacity of the zinc-manganese battery before 200 cycles, indicating that the introduction of manganese sulfate can inhibit the dissolution of the positive electrode material and improve the reversibility of the zinc-manganese battery. After 500 cycles of using the electrolyte, the capacity only decayed a little, and the performance was far better than other electrolytes.
[0067] Comparative Example 3
[0068] Compared with Example 1A, the only difference is that the sulfuric acid-modified diatomaceous earth in the electrolyte is replaced by the diatomaceous earth before modification, and the other operations and parameters are the same as those in Example 1. SEM images of the diatomaceous earth before and after modification are shown in FIG. Figure 6 ; Figure 6 a is before modification, Figure 6 b is after modification.
[0069] Repeat this process to assemble three batches of batteries. Tests were performed using the method of Example 1. The test performance is shown in Figure 7 .
[0070] Figure 7The graph shows the cycle performance of the battery made of the electrolyte material prepared with untreated diatomite. At a current density of 200 mA / g, the capacity of the first sample dropped sharply after 100 cycles. The second sample was overcharged after about 120 cycles, and the battery was broken. After 500 cycles, the capacity retention rate of the third sample reached 72.9%, which was lower than 86.2% in Example 1. This shows that the performance of the electrolyte prepared with unmodified diatomite is unstable and far inferior to that of the modified diatomite.
[0071] Comparative Example 4
[0072] Compared with Example 1A, the only difference is that the sulfuric acid-modified diatomaceous earth is replaced by an equal weight of hydrochloric acid-modified diatomaceous earth, and the modification method of the hydrochloric acid-modified diatomaceous earth is similar to the sulfuric acid-modified diatomaceous earth method, the only difference is that the acid in the acid treatment stage is hydrochloric acid of equal mass concentration. Other operations and parameters are the same as in Example 1.
[0073] Figure 8 It is a graph showing the cycle performance of the battery made of the electrolyte material of Comparative Example 4. At a current density of 200 mA / g, the capacity of the battery using the hydrochloric acid-modified electrolyte decayed rapidly after 250 cycles, and the long cycle performance was not as good as that using the sulfuric acid-modified electrolyte.
Claims
1. An electrolyte for an aqueous zinc-manganese battery, characterized in that: The invention comprises diatomaceous earth modified by sulfuric acid, zinc salt, manganese salt and water, wherein the content of the diatomaceous earth modified by sulfuric acid is 5-25wt%.
2. The electrolyte according to claim 1, characterized in that The diatomaceous earth is pre-washed with water and then modified by soaking in sulfuric acid, followed by solid-liquid separation and water washing to obtain the sulfuric acid-modified diatomaceous earth.
3. The electrolyte according to claim 3, characterized in that The concentration of the solute in the sulfuric acid solution is 5 to 20 wt.%.
4. The electrolyte according to claim 2, characterized in that The soaking process is carried out under stirring; Preferably, the soaking time is 6 to 24 hours; preferably 10 to 15 hours.
5. The electrolyte according to claim 1, characterized in that The zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc trifluoromethanesulfonate, zinc nitrate and zinc perchlorate.
6. The electrolyte according to claim 1, characterized in that The manganese salt is one or more of manganese sulfate and manganese chloride.
7. The electrolyte according to claim 1, 5 or 6, characterized in that In the electrolyte, the concentration of the zinc salt is 1 mol / L to 10 mol / L, preferably 1.5 mol / L to 2.5 mol / L; The concentration of the manganese salt is 0.05 mol / L to 0.5 mol / L, and more preferably 0.075 mol / L to 0.125 mol / L; The content of the sulfuric acid-modified diatomaceous earth is 5-25wt%.
8. A method for preparing an electrolyte according to any one of claims 1 to 7, characterized in that: The diatomaceous earth, zinc salt, manganese salt and water are mixed evenly; Preferably, the mixing process is carried out with the assistance of stirring and / or ultrasound.
9. Use of the electrolyte according to any one of claims 1 to 7, characterized in that: It is used as an electrolyte to prepare aqueous zinc-manganese batteries; Preferably, in the aqueous zinc-manganese battery, the manganese element in the electrolyte is 0.9 to 2.5 times the weight of the manganese element in the positive electrode of the aqueous zinc-manganese battery; preferably 0.95 to 1.1 times.
10. An aqueous zinc-manganese battery, characterized in that: It comprises the electrolyte according to any one of claims 1 to 7.
